ANALISIS KEBUTUHAN MODAL KERJA DITINJAU DARI TINGKAT PERPUTARAN OPERASI PERUSAHAAN PADA PDAM KABUPATEN BANYUMAS DAN PURBALINGGA - Titi Nurfitri; Sri Lestari; Arifin Mukti (Faculty of Economics and Business Universitas Jenderal Soedirman, 2010)
Basically, the notion of working capital is capital needed by companies to finance operations daily. Working capital requirements for an enterprise can be reflected in the large-scale sales. With sales of large-scale owned by the company can determine the level of activity of company operations. This study aims to determine and analyze the trend of working capital turnover in terms of sales levels and trends in working capital requirements in terms of turnover at the company's operations and taps Purbalingga and Banyumas. The problem is limited to the functional working capital cash, inventories and trade receivables. The data is the data collected during the nine years from 1999 to 2007. Based on research results is known that the turnover of working capital in Banyumas taps and Purbalingga from 2000 to 2007 tended to decline when accompanied by an increase in sales, while working capital requirements in terms of working capital turnover in the taps and Purbalingga and Banyumas tends to increase. From this study suggested that taps Banyumas and Purbalingga must see to it that the rotation period of their working capital is not too long and should be more concentrated on the amount of sales levels in order to meet working capital requirements in accordance with the level of corporate activity.